Identidades masculina e sertaneja e sua relação com o sexismo e cultura da honra no sertão sergipano - Souza, Charles Vinicius Bezerra de (2020)
The main objective of this thesis was to analyze sertanejo and masculine identities of men from Sergipe’s sertão and their relationship with sexism and culture of honor. Based on the hypothesis that there is a positive correlation relation between those identity representations, culture of honor and sexism. The empirical part was composed by a study in which 117 students from a university in Sergipe’s sertão participated, all of them being male and residents in the semiarid region of Northeast. For data collection a questionnaire was used containing: sociodemographic data, an instrument of free evocation of words based on Zavalloni’s Psychosocial Identity Inventory (1984), the Conceptions of Masculinity Scale (Oransky & Fisher, 2009), the Ambivalent Sexism Inventory (Glick & Fiske, 1996) and an instrument about Conjugal Honor developed by us. The results indicate that the identity representations about sertanejo were featured by traits that emphasizes strength and resilience, image associated to representations shared by Sertão and its people, identified in popular imaginary as a “problem” region. In the identity representations related to men’s it was perceptible a gender constitution that is linked to the maintenance of the patriarchal structure, which reinforces the idea of a hegemonic masculinity, reaffirming the male superiority to the detriment of the female, bound by a stereotypical perspective of “fragile femininity’. We also found a positive correlation between culture of honor, sexism and the conceptions of masculinity, as these constructs are also related to masculine and sertanejo identities, showing that this way of conceiving masculinity and its association between sexism and the defense of honor suggest a naturalization of traditional sexism practices and violent behaviors in defense of reputation. However, it was not found sexism in those identified with the sertão, and low adhesion to culture of honor, that is, the results show that defense of honor is a bigger predictor of sexist behaviors than sertanejo identity. These results were analyzed from the theory of Social Identity Theory, of Henri Tajfel (1982).